2005
DOI: 10.1103/physrevb.71.235207
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the antiferromagnetic semiconductorMnSb2S4

Abstract: The electronic band structures of orthorhombic ͑oP28͒ and monoclinic ͑mC28͒ MnSb 2 S 4 were investigated with ab initio calculations in the local spin density approximation to the density functional theory. An analysis of the electronic properties and of the chemical bonding is provided using the augmented spherical wave method considering nonmagnetic, ferromagnetic, ferrimagnetic, and antiferromagnetic model orderings. In agreement with experimental results both modifications of MnSb 2 S 4 are predicted to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The homologous MnSb 2 Se 4 mC28 could also be obtained by solid state preparation [5]. Spin polarized DFT calculations confirmed the semiconducting behaviour of both phases of MnSb 2 S 4 [5,6]. Neutron powder diffraction experiments on MnSb 2 S 4 mC28 and the heavier homologous compounds revealed that these compounds become antiferromagnetic below about 25 K. The magnetic spins show a complicated helical ordering pattern [5,7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The homologous MnSb 2 Se 4 mC28 could also be obtained by solid state preparation [5]. Spin polarized DFT calculations confirmed the semiconducting behaviour of both phases of MnSb 2 S 4 [5,6]. Neutron powder diffraction experiments on MnSb 2 S 4 mC28 and the heavier homologous compounds revealed that these compounds become antiferromagnetic below about 25 K. The magnetic spins show a complicated helical ordering pattern [5,7].…”
Section: Introductionmentioning
confidence: 94%
“…The different radii of the constituting ions have obviously a certain influence on the structural arrangement of the resulting compounds. Thus, we find two different types of octahedra MnSe 6 and MnSe 2 I 4 in MnSbSe 2 I but only one type of octahedra MnS 4 Cl 2 in MnSbS 2 Cl. The different octahedra in MnSbSe 2 I share common edges formed either by two Se atoms or by two I atoms, respectively,.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, electrical-conductivity and magneticsusceptibility measurements revealed that MnSb 2 S 4 is a semiconducting antiferromagnet with a Néel temperature (T N ) of 26.5 K and an energy bandgap (E g ) of 0.77 eV. [15][16][17] By modifying the nature of the Sb-S bonds that connect the magnetic and semiconducting subunits in MnSb 2 S 4 through isoelectronic substitution of S by Se, we anticipate a significant alteration in electronic charge transport as well as the nature of coupling between adjacent magnetic chains. For instance, an energy bandgap smaller than that of MnSb 2 S 4 (E g = 0.77 eV) and high electrical conductivity are expected for MnSb 2 Se 4 due to an increase in the degree of covalency of the Sb-Se bond.…”
Section: Introductionmentioning
confidence: 99%
“…The different radii and different ionicities of the constituting ions have obviously a certain influence on the structural arrangement of the resulting compounds. Thus, we find two different types of octahedra MnSe 6 and MnSe 2 I 4 in MnPnSe 2 I (Pn ¼ Sb, Bi) but only one type of octahedra MnS 4 Cl 2 in MnSbS 2 Cl. The different octahedra in MnPnSe 2 I share common edges formed either by two Se atoms or by two I atoms, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…MnSb 2 Se 4 mC28 could also be obtained by solid state preparation [5]. MnSb 2 S 4 is a semiconductor and spin polarized DFT calculations confirmed the semiconducting behaviour of both phases of MnSb 2 S 4 [5,6]. Neutron powder diffraction experiments on MnSb 2 S 4 mC28 and the heavier homologous compounds revealed that they show antiferromagnetic ordering below 25 K with a complicated helical ordering pattern [5,7].…”
Section: Introductionmentioning
confidence: 99%